# Kinetic energy or momentum?

I'm really confused! After a collision, how would I know which formulas to use? I noticed this a few days ago, but when I use the conservation of energy to calculate the final speed of an object, the answer would be different from using conservation of momentum.
I don't know why I noticed this a few days...
show more
I'm really confused! After a collision, how would I know which formulas to use? I noticed this a few days ago, but when I use the conservation of energy to calculate the final speed of an object, the answer would be different from using conservation of momentum.

I don't know why I noticed this a few days ago (tomorrow is my exam), I've been using kinetic energy and momentum for 3 courses now >.>

Someone please help explain when I should use momentum vs kinetic energy..

I don't know why I noticed this a few days ago (tomorrow is my exam), I've been using kinetic energy and momentum for 3 courses now >.>

Someone please help explain when I should use momentum vs kinetic energy..

Update:
Okay, here is an example:
a car of mass m collides with a stationary truck of mass M
the car's initial velocity is Vi. The car's final velocity is 0
find the truck's final velocity
so if I do momentum
p1i + p2i = p1f + p2f
p1i + 0 = 0 + p2f
mVi = MVf
(m/M)*Vi = Vf
But if I use kinetic energy
K1i +...
show more
Okay, here is an example:

a car of mass m collides with a stationary truck of mass M

the car's initial velocity is Vi. The car's final velocity is 0

find the truck's final velocity

so if I do momentum

p1i + p2i = p1f + p2f

p1i + 0 = 0 + p2f

mVi = MVf

(m/M)*Vi = Vf

But if I use kinetic energy

K1i + K2i = K1f + K2f

K1i + 0 = 0 + K2f

0.5*m*Vi^2 = 0.5*M*Vf^2

[(m/M)*Vi^2]^0.5 = Vf or Vf = Vi*((m/M)^0.5)

^0.5 is square root

Clearly, I got a different answer....

a car of mass m collides with a stationary truck of mass M

the car's initial velocity is Vi. The car's final velocity is 0

find the truck's final velocity

so if I do momentum

p1i + p2i = p1f + p2f

p1i + 0 = 0 + p2f

mVi = MVf

(m/M)*Vi = Vf

But if I use kinetic energy

K1i + K2i = K1f + K2f

K1i + 0 = 0 + K2f

0.5*m*Vi^2 = 0.5*M*Vf^2

[(m/M)*Vi^2]^0.5 = Vf or Vf = Vi*((m/M)^0.5)

^0.5 is square root

Clearly, I got a different answer....

Follow

3 answers
3

Are you sure you want to delete this answer?